2015
DOI: 10.1016/j.ijppaw.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Ventral dermatitis in rowi (Apteryx rowi) due to cutaneous larval migrans

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…scratching), ectoparasites as well as primary and secondary bacterial infections. In Rowi (Apteryx rowi), a cutaneous larva migrans of Trichostrongylus species was detected as causal agent of dermatitis (Gartrell et al 2015). Another possible factor has been described in turkeys that were immunosuppressed by virus infections with subsequent impaired cutaneous antimicrobial barrier and increased susceptibility for opportunistic pathogens, like clostridial infections (Huff et al 2013;Thachil et al 2014).…”
Section: Pathologymentioning
confidence: 99%
“…scratching), ectoparasites as well as primary and secondary bacterial infections. In Rowi (Apteryx rowi), a cutaneous larva migrans of Trichostrongylus species was detected as causal agent of dermatitis (Gartrell et al 2015). Another possible factor has been described in turkeys that were immunosuppressed by virus infections with subsequent impaired cutaneous antimicrobial barrier and increased susceptibility for opportunistic pathogens, like clostridial infections (Huff et al 2013;Thachil et al 2014).…”
Section: Pathologymentioning
confidence: 99%
“…Cutaneous larval migrans has been described in brown kiwi chicks held on a crèche island as part of a captive propagation program (Gartrell et al, 2015). Infection was associated with feather loss, and a "scurfy" dermatitis was present in the abdominal area and along the vent margin.…”
Section: Metazoamentioning
confidence: 99%
“…Histology of skin biopsies taken from several of the affected birds showed nematodes present within the epidermis, suggesting the condition cutaneous larva migrans . Molecular sequencing of nematode DNA extracted from the biopsies aligned among Trichostrongylus spp; however, the authors concluded that this result should be viewed with caution as concurrent morphological evaluation was limited and members of this nematode genus have not previously been associated with cutaneous migratory lesions ( Gartrell et al, 2015 ).…”
Section: Introductionmentioning
confidence: 98%
“…In the case of rowi, ONE chicks are raised on a single off-shore crèche island where they are intermittently monitored by DOC rangers. In 2013, 15 out of 30 juvenile rowi on the crèche island developed a crusting dermatitis affecting the ventral abdominal skin and vent margin ( Gartrell et al, 2015 ). Histology of skin biopsies taken from several of the affected birds showed nematodes present within the epidermis, suggesting the condition cutaneous larva migrans .…”
Section: Introductionmentioning
confidence: 99%